1996
DOI: 10.1080/15216549600201193
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the shikimate‐3‐phosphate interacting site in the N‐terminal domain of 5‐enolpyruvyl shikimate‐3‐phosphate synthase of Bacillus subtilis

Abstract: Summary. The role of basic amino acid residues that are highly conserved in the Nterminal domain of 5-enolpyruvyl shikimate-3-phosphate synthase (EPSPs) in the binding of the substrate, shikimate-3-phosphate, has been assessed. Lys 19 and Arg 24 in the Bacillus subtilis EPSPs were substituted by glutamic acid and aspartic acid residues respectively by site-directed mutagenesis. Native and the mutant proteins were expressed using a two-vector system and the expressed proteins were purified to near homogeniety. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…In this study, only the lysine to arginine mutant protein exhibited enzymatic activity (15% of that of wild-type EPSPS), while the K22A and K22E mutant proteins were catalytically inactive. A critical role of lysine 22 was also confirmed by recent investigations of the corresponding mutant protein from Bacillus subtilis (8) and Escherichia coli (9). Characterization of these mutant proteins indicated a role of this lysine in binding of the substrate S3P.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…In this study, only the lysine to arginine mutant protein exhibited enzymatic activity (15% of that of wild-type EPSPS), while the K22A and K22E mutant proteins were catalytically inactive. A critical role of lysine 22 was also confirmed by recent investigations of the corresponding mutant protein from Bacillus subtilis (8) and Escherichia coli (9). Characterization of these mutant proteins indicated a role of this lysine in binding of the substrate S3P.…”
mentioning
confidence: 61%
“…Binding of UDP-N-Acetylglucosamine (UDPNAG) to Wild-Type and Mutant Proteins. In light of the recent finding that mutation of a lysine in an equivalent position in EPSPS resulted in the loss of S3P binding capacity ( , ), we set out to investigate characteristics of the binding of UDPNAG to the K22 mutant proteins. Dissociation constants for binding of UDPNAG to wild-type MurA and mutant proteins were determined by isothermal titration calorimetry (ITC).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism shown in Scheme 1B postulates the involvement of an enzyme nucleophile, no evidence was presented by Studelska et al ( 1) that a candidate residue had been identified. Many of the residues in the enzyme active site have already been identified (8)(9)(10)(28)(29)(30)(31)(32)(33)(34), and those that are potential nucleophiles have been ruled out as being catalytically irrelevant. Indeed, Studelska et al 1) fail to point out that Anderson, Walsh, and co-workers first reported the detection of a noncovalent tetrahedral intermediate (36).…”
Section: Discussionmentioning
confidence: 99%
“…A shikimate 3-phosphate interacting site has been located in the N-terminal domain. 29 A mutant strain of E. coli EPSP synthase in which His-385 is replaced with asparagine is much less catalytically competent (6% activity) than the corresponding glutamine mutant, previously shown to retain some 25% activity. 30 Accordingly, the -nitrogen of histidine is suggested to play a role in catalysis, perhaps by hydrogen-bonding to another residue that complexes the substrates or products.…”
Section: Shikimate Kinasementioning
confidence: 97%